Evaluation of bone mineral density and bone turnover in children on anticoagulation - Thom, Katharina; Patsch, Janina Maria; Haufler, Florentina; Pees, Christiane; Albinni, Sulaima; Weber, Michael; Male, Christoph; Raimann, Adalbert (Frontiers in Endocrinology, 2023)
Background Childhood and adolescence are critical periods of bone mineral acquisition. Children on anticoagulation (AC) might have an increased risk for reduced bone mineral density (BMD). Risk factors for impaired bone accumulation include chronic diseases, immobility, and medication. Vitamin K (VK) deficiency reflected by undercarboxylated osteocalcin levels (ucOC) has been identified as a predictor of osteoporosis and fractures. Data on bone health in children under AC are sparse. Aims To evaluate BMD in children on AC and characterize the risk factors of low BMD, including VK and Vitamin D (VD) status. Methods Single-center cross-sectional study of clinical, biochemical, and densitometric parameters. Assessment of VK surrogate parameters included ucOC and matrix gla protein (MGP). Results A total of 39 children (4–18 years; 12 females) receiving AC were included, 31 (79%) on VK antagonists and 8 (21%) on direct oral anticoagulants. Overall, BMD was decreased for both the lumbar spine (LS; −0.7SDS) and total body less head (TBLH; −1.32SDS) compared with pediatric reference data. Significant associations were found between early pubertal development and TBLH-BMD, and between BMI and LS-BMD. VK surrogate parameters were highly related to patients’ age and pubertal development. Neither serum parameters nor AC-related factors predicted BMD. VD was detected in 10/39 patients with lower values during puberty. Conclusion Our data indicate BMD reduction in pediatric patients on AC. Although AC-related factors did not predict reduced BMD, low BMI and pubertal stages represented important risk factors. Awareness of risk factors for low BMD and high prevalence of VD deficiency during puberty could contribute to the improvement of bone health in this vulnerable patient group.